SANTIAGO MONTOBBIO, Poesía en Roma, Alhaurín el Grande, El Bardo, 2018, 542 pp. - Balcells, José María (Lectura y signo, 2019)
Reseña de SANTIAGO MONTOBBIO, Poesía en Roma, Alhaurín el Grande, El Bardo, 2018, 542 pp.